1978
DOI: 10.1136/bmj.1.6108.279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quinidine on plasma concentrations of digoxin.

Abstract: A 74-year-old woman weighing 48 kg was admitted for a simple mastectomy 14 months after advanced carcinoma of the breast had been treated by radiotherapy. She was in good general health, her only complaint being dyspnoea on exertion. Examination showed a pansystolic murmur, which was attributed to mild mitral incompetence. Arterial pressure was 180/ 65 mm Hg. There was no evidence of cardiac failure, but an electrocardiogram contained some evidence of myocardial ischaemia. Haemoglobin was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
2

Year Published

1979
1979
1991
1991

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(35 citation statements)
references
References 1 publication
2
31
0
2
Order By: Relevance
“…Studies in this hospital pointed out the possibility that a pharmacokinetic drug interaction between quinidine and digoxin may partially explain this side-effect. It was found that the plasma digoxin levels increased when quinidine was added to the therapy (Ejvinsson, 1977(Ejvinsson, , 1978a(Ejvinsson, , 1978b. This finding has been independently confirmed by other investigators (Leahey, Reifell, Drusin, Heissenbuttel, Lovejoy & Bigger, 1978).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Studies in this hospital pointed out the possibility that a pharmacokinetic drug interaction between quinidine and digoxin may partially explain this side-effect. It was found that the plasma digoxin levels increased when quinidine was added to the therapy (Ejvinsson, 1977(Ejvinsson, , 1978a(Ejvinsson, , 1978b. This finding has been independently confirmed by other investigators (Leahey, Reifell, Drusin, Heissenbuttel, Lovejoy & Bigger, 1978).…”
Section: Introductionmentioning
confidence: 74%
“…Data from 12 of these patients have been published in preliminary reports (Ejvinsson, 1977(Ejvinsson, , 1978b. In two of the patients quinidine treatment had to be discontinued after 12 h due to ventricular tachycardia and/or ventricular fibrillation.…”
mentioning
confidence: 99%
“…This decrease in the affinity of the receptor for digoxin under nonsaturating conditions should increase serum digoxin concentration as long as quinidine is present. Although the extent to which in vivo bound digoxin levels would decrease is unclear, it should be pointed out that, because <1% of the total body glycoside stores are present in the serum of digoxin-treated patients (44), a loss of 1% of tissue digoxin stores could result in a twofold increase in serum digoxin concentration, and would approximate the increase frequently noted clinically following quinidine administration (1,2,4,7,8,(11)(12)(13)(14)(15). The precision of our experiments on purified Na,K-ATPase (Table V) and in a previous study (32), is significantly slower than its dissociation rate from receptors in skeletal and cardiac muscle (45), tissues containing the major pools of glycoside binding sites in man (44).…”
Section: Resultsmentioning
confidence: 99%
“…Since the unexpected discovery that quinidine causes a marked increase in the steady-state plasma concentration of digoxin (Ejvinsson, 1977;Kaufman 1978;Ejvinsson 1978;Leahey, Reiffel, Drusin, Heissenbuttel, Lovejoy & Bigger, 1978;Doering & Konig, 1978) work has progressed to clarify the underlying mechanisms. It was shown that quinidine also exerts this effect in patients where digoxin maintenance therapy was discontinued 2 days before quinidine treatment suggesting redistribution as a mechanism (Leahey et al, 1978;Dahlqvist, Ejvinsson & Schenck-Gustafsson, 1980).…”
Section: Introductionmentioning
confidence: 99%